Test of Fruit Picker Tool on Different Types fruit trees - Yuki Febrina Sirait; Saipul Bahri Daulay; Adian Rindang; Edi Susanto (Universitas Sumatera Utara, 2013)
This research is about fruit picker tool on different type of fruit trees. This research was conducted to test the fruit picker tool on various type of fruit trees i.e melinjo, tamarind and rambutan to determine the effective capacity of the tool, the percentage of defects and field capacity of the tool. The research was conducted in Tridharma, A. H. Nasution and Bunga Mawar Roads from February to August 2012 using non-factorial completely randomized design with melinjo, tamarind and rambutan trees. The parameters measured were the effective capacity of the tool, the percentage of defect and tool field capacity tool. The results Showed various types of fruit trees had highly significant effect on the effective capacity of the tool and the percentage of defect had no significant effect on the capacity of the field. The best result was on rambutan fruit i.e 30.54 kg h-1 with the percentage of defects of 7.3%.